Reversible Switching of Single-Molecule Magnetic Behaviour by Desorption/Adsorption of Solvent Ligand in a New Dy(III)-Based Metal Organic Framework - Song, Xiao-Jiao; Hu, Zhao-Bo; Li, Miao-Miao; Feng, Xin; Kong, Ming; Xue, Xiao-Ming; Zhang, Yi-Quan; Song, You (Frontiers in Chemistry, 2021)
Two metal-organic frameworks (MOFs), [Dy(BDC)(NO3)(DMF)2]n (1, H2BDC = terephthalic acid) and [Dy(BDC)(NO3)]n (1a), were synthesized. The structures of MOFs 1 and 1a are easy to be reversibly transformed into each other by the desorption or adsorption of coordination solvent molecules. Accordingly, their magnetic properties can also be changed reversibly, which realizes our goals of manipulating on/off single-molecule magnet behaviour. MOF 1 behaves as a single-molecule magnet either with or without DC field. Contrarily, no slow magnetic relaxation was observed in 1a both under zero field and applied field.